2021
DOI: 10.1016/j.jamcollsurg.2021.08.692
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the WHO Surgical Safety Checklist Relative to Its Design and Intended Use: A Systematic Review and Meta-Meta-Analysis

Abstract: BACKGROUND:The aim of this study was to identify what parts of the World Health Organization Surgical Safety Checklist (WHO SSC) are working, what can be done to make it more effective, and to determine if it achieved its intended effect relative to its design and intended use. STUDY DESIGN: We conducted a qualitative thematic analysis and meta-meta-analyses of findings in WHO SSC systematic reviews following Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. RESULTS:Twenty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 49 publications
1
23
0
Order By: Relevance
“…A recent systematic review and meta-analysis done by Sotto and colleagues (2021) reported that team members found the SCCL to increase situational awareness by facilitating the exchange of information regarding the patient's history, risk and required procedure. This review also found overwhelmingly positive reports on the effect of the SSCL on teamwork, team dynamics and communication (Sotto et al, 2021).…”
Section: Contributions and Impactmentioning
confidence: 89%
See 1 more Smart Citation
“…A recent systematic review and meta-analysis done by Sotto and colleagues (2021) reported that team members found the SCCL to increase situational awareness by facilitating the exchange of information regarding the patient's history, risk and required procedure. This review also found overwhelmingly positive reports on the effect of the SSCL on teamwork, team dynamics and communication (Sotto et al, 2021).…”
Section: Contributions and Impactmentioning
confidence: 89%
“…However, other studies showed no association between checklist use and similar outcomes (Urbach et al, 2014;Gama et al, 2019). While the results are mixed regarding the effectiveness of the SSCL at improving clinical outcomes, there is a general agreement that the SSCL improves the perception of teamwork, communication, situational awareness, and safety climate in the OR (Haynes et al, 2011, Khoshbin et al, 2009, Sotto et al, 2021 Copyright 2022 by Human Factors and Ergonomics Society. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…When used well, the WHO SSC has a demonstrated association with the clinical outcomes addressed within it but is not associated outcomes that are not directly addressed (eg, deep vein thrombosis prophylaxis). 12 With this in mind, the ERAS SSC was designed to ensure that discussions addressing specific issues important to a patient's recovery are discussed at 3 defined, critical points in perioperative care. This new checklist has introduced new elements critical to patient safety and optimal recovery.…”
Section: Discussionmentioning
confidence: 99%
“…11 Both tools have demonstrated consistent associations with improved surgical safety and outcomes, particularly within colorectal and gynecologic surgery, where ERAS is best-studied. [12][13][14] ERAS guidelines often consist of upwards of 20 items designed to be implemented as a care bundle. The level of adherence correlates with outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation